Assessing the Current Healthcare System Capacity in Kosovo to Address Potential Risks of Climate Change Extremes - Mehmeti-Cakuli , Lendita; Dimovska, Mirjana; Gjorgjev, Dragan (Open Access Macedonian Journal of Medical Sciences, 2024)
BACKGROUND: Climate change (CC) threats to public health in Kosovo include changes in rainfall and extreme weather conditions (heat waves, rising average temperatures, floods, and droughts). Such changes can affect the physical, mental health, and well-being of the population, also potentially adversely affecting the functioning and physical infrastructure of the healthcare system. AIM: The aim of the study was to conduct a CC vulnerability assessment in selected healthcare facilities and workforce in Kosovo. METHODS: The World Health Organization standard checklist was used to assess weaknesses and level of preparedness in six healthcare facilities in the context of CC for three extreme situations of exposure (heat waves, floods, and droughts). RESULTS: During heat waves and floods the weak points identified are: The infrastructure, technology process, healthcare workforce preparedness, and process of waste treatment. In some regions (Mitrovica and Peja), the risk is even higher in the absence of sufficient health staff. The hospital in Gjilan shows the highest level of unpreparedness to cope some CC extremes. The western part of the country has a higher risk of frequent floods. The lack of an emergency plan to protect health workers from numerous biological and chemical risks increases the risk of negative effects of floods. CONCLUSIONS: The findings of this study confirm various types of vulnerabilities and weaknesses in the healthcare facilities in Kosovo for all areas of assessment (health workforce preparedness, level of adaptation of the current system, infrastructure, technologies, and sustainability). The health outcomes of CC jeopardize the provision of good quality healthcare services. A short list of priorities is recommended to minimize the various types of vulnerabilities.